Making the invisible visible: methods to enhance features of tiny spider webs - Solano Brenes, Diego (2018)
The characteristics and designs of webs provide valuable information on ecology, behavior and phylogenetic relationships. Characters are often obtained from detailed analyses of web photographs. We describe new methods to enhance web visibility; they consisted of painting the inner surfaces of Petri dishes with an opaque black spray paint that produced a rough surface, and then applying a salt spray from a nebulizer or fine white powder to tiny webs constructed in there. Using these methods on webs of Oecobius concinnus Simon, 1893, we discerned several unknown details of the refuge and cribellar threads that had previously gone undetected.